Simulation of Bonded Joints Failure using Progressive Mixed-Mode Damage Models - M. F. S. F. de Moura (2013)
In the most recent years, structural applications of bonded joints have increased remarkably owing to their several advantages relative to other joining methods. As a consequence, the development of improved models to provide design effi ciency and, at the same time, increase the confi dence of designers acquires special relevancy. Recent developments considering cohesive and continuum mixed-mode damage models have demonstrated that these methods are able to deal with several details inherent to mechanical behaviour of bonded joints. Both methods allow simulation of damage initiation and propagation by combining classical strength of materials approaches with fracture mechanics concepts. In this work, several different mixed-mode cohesive laws adapted to different types of adhesives mechanical behaviour are presented and discussed. Effectively, while mechanical behaviour of brittle or moderately ductile adhesives is well simulated by means of the simple bilinear cohesive law, adhesives with pronounced ductile behaviour require more sophisticated cohesive laws. The aspects regarding determination of some cohesive parameters are also given special attention in the present paper. A continuum mixed-mode damage model is also presented using the bilinear softening cohesive law. This model is advantageous since properties degradation takes place inside solid elements used to simulate the adhesive, which allows the evaluation of specifi c issues like the infl uence of asymmetric propagation on joint mechanical behaviour in a more realistic manner. Important conclusions about advantages and drawbacks of both methodologies are drawn.